Understanding the Bible - Stott, John R. W. (Minneapolis : World Wide Publications, 1972)
Lloyd M. Perry Collection.
"Special Crusade ed., published for the Billy Graham Evangelistic Association."
Keywords: Bible -- Study and teaching; Bible -- Criticism and interpretation